CLUE: An Observational Checklist for Usability Evaluation of Multimodal Games for Children Who Are Blind - Darin, Ticianne; Andrade, Rossana; Sánchez, Jaime (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4226, 2018)
This paper summarizes the proposal and validation of a Checklist for Usability Evaluation of Multimodal Games for Children who are Blind (CLUE). CLUE was designed to assist researchers and practitioners in usability evaluation field studies involving people who are blind, addressing multiple aspects of gameplay and multimodality, including audio, graphics, and haptics. Overall, initial evidence indicates that the use of CLUE during user observation helps to raise a greater number of relevant usability issues than other methods such as interview and questionnaire.